2016
DOI: 10.3847/2041-8213/833/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Polarized Quasi-Periodic Microstructure Emission in Millisecond Pulsars

Abstract: Microstructure emission, involving short timescale, often quasi-periodic, intensity fluctuations in subpulse emission, is well known in normal period pulsars. In this Letter, we present the first detections of quasi-periodic microstructure emission from millisecond pulsars (MSPs), from Giant Metrewave Radio Telescope observations of two MSPs at 325 and 610 MHz. Similar to the characteristics of microstructure observed in normal period pulsars, we find that these features are often highly polarized and exhibit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
3
14
2
Order By: Relevance
“…observing with sufficient time resolution reveals that individual pulses are often composed of a collection of separate µswide subpulses (micropulses, also dubbed "microstructure", e.g., Hankins 1971). Micropulses have been recorded from a substantial fraction of strong nearby pulsars and are speculated to be a common trait of pulsar radio emission (Lange et al 1998;Popov et al 2002;Kuzmin et al 2003;De et al 2016). Their origin is still as unknown as the GP formation mechanism; although some studies link these phenomena (Petrova 2004a,b).…”
Section: Pulse Duration and Brightness Temperaturementioning
confidence: 99%
“…observing with sufficient time resolution reveals that individual pulses are often composed of a collection of separate µswide subpulses (micropulses, also dubbed "microstructure", e.g., Hankins 1971). Micropulses have been recorded from a substantial fraction of strong nearby pulsars and are speculated to be a common trait of pulsar radio emission (Lange et al 1998;Popov et al 2002;Kuzmin et al 2003;De et al 2016). Their origin is still as unknown as the GP formation mechanism; although some studies link these phenomena (Petrova 2004a,b).…”
Section: Pulse Duration and Brightness Temperaturementioning
confidence: 99%
“…Many authors have observed that the characteristics of GHz radio emission, including polarization and the large negative spectral indices, are broadly similar over wide intervals of surface magnetic flux density, from 10 8 G in the MSP to more than 10 13 G. This should be in itself sufficient to prompt questions about theories of the emission process that are based on electron-positron pair production. The very recent addition of microstructure to the list by De et al (2016) reinforces this. The ion-proton polar cap is concomitant with the plasma composition that basic nuclear interactions must produce in Ω · Bs < 0 neutron stars.…”
Section: Resultsmentioning
confidence: 70%
“…Roy & Pal (2013) discovered possibly the youngest supernova remnant at 330 MHz in our Galaxy. De et al (2016) detected polarized quasi-periodic microstructure emission in millisecond pulsars. Recently, Saxena et al (2018) have discovered the most distant radio galaxy identified to date at a redshift of z = 5.72.…”
Section: The Giant Metrewave Radio Telescopementioning
confidence: 98%